2023
DOI: 10.1002/fft2.260
|View full text |Cite
|
Sign up to set email alerts
|

Feeding the microbiota–gut–brain axis: Nucleotides and their role in early life

Abstract: Nucleotides ingested from breast milk and complementary foods during infancy play a vital role in the development of the immune and nervous system, as well as the maturation of gut function, and are considered a “special dietary nutrient.” Based on the existing research progress and theoretical basis, this review takes the distribution of dietary nucleotides (NTs) in the early life (after birth to the age of 3 years) diet and the in vivo metabolism/absorption process as the starting point and expounds on its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Contrary to HFD, supplementation of nucleotides, found in human milk, enhanced neuro-maturation in the prefrontal cortex and hippocampus in rats. This was mediated by gut microbiota composition and function and correlated to neurodevelopmental phenotypes [32].…”
Section: Recent Evidence In Animalsmentioning
confidence: 98%
“…Contrary to HFD, supplementation of nucleotides, found in human milk, enhanced neuro-maturation in the prefrontal cortex and hippocampus in rats. This was mediated by gut microbiota composition and function and correlated to neurodevelopmental phenotypes [32].…”
Section: Recent Evidence In Animalsmentioning
confidence: 98%
“…In comparison, infants fed through alternative methods demonstrated elevated levels of fecal metabolites such as adenine and orotic acid . In our previous study, we found that the intake of dietary NTs may have multiple correlations on the formation of early gut microbiota and brain development …”
Section: Introductionmentioning
confidence: 99%
“…14 In our previous study, we found that the intake of dietary NTs may have multiple correlations on the formation of early gut microbiota and brain development. 15 The nutrients in milk and early diet are important external factors that influence the healthy development of the GM−gut− brain interface. 16 For example, oligosaccharides and polyunsaturated fatty acids in milk have been directly linked to the development of infants' GM−gut−brain axis and are noted to promote infant brain development, GM formation, and intestinal health.…”
Section: Introductionmentioning
confidence: 99%